Carnival Land: A Performance of Metaphors - Tavares, Tatiana (Auckland University of Technology, 2011)
"Carnival Land" is a body of work formatted as a graphic novel that weaves together photomontage and storytelling. Based on my recent experiences as an immigrant to New Zealand, it provides a fictional narrative in metaphors. The story tells of the trials and eventual transformation of a young girl in a foreign land, where aspirations appear as costumes in an annual Carnival parade. The work is conceived as a transformative journey where bricolaged identity plays out in theatricised environments. Using autoethnography as a methodological framework, the resulting novel is a creative orchestration of bilinguality, metaphor and theatricised multi-page spreads. [Note: the novel is embargoed until 31 March 2015]
Keywords: Carnival; Immigration; Bricolage; Rites of passage; Theater; Performance; Metaphor; Identity; Transformative journey; Narrative; Story telling; Autoethonography; Heuristics; Reflexive; Graphic design; Photomontage; Illustration